Changes in internal structure and nutritional quality with different types of maize kernels during Grain filling period (Bangladesh Journal of Botany, 2023)
To understand the changes in grain internal structure and nutrients during maize filling, Jingkenuo 2000 (waxy corn), Chaosweet 2000 (sweet corn), and Zhengdan 958 (common corn) were used as test materials. This study observed the internal structure of the corn grain and measured the change in nutritional quality during the filling period. Throughout the determination stage, the starch granules did not fill the whole endosperm cell in Chaosweet 2000, and the cell wall was clearly visible. By contrast, the starch granules filled the whole endosperm cell in Jingkenuo 2000 and Zhengdan 958. The protein content in Chaosweet 2000 was significantly (P